THE COMPARISON OF USING JUMBLE WORDS AND WORD ORDER TECHNIQUES TOWARD STUDENTS’ GRAMMAR MASTERY - BUNGSUDI BUNGSUDI; EVA FALIYANTI (Sriwijaya University Learning and Education International Conference, 2016)
Grammar is one of basic language components to produce an appropriate sentenceformally. Many students are difficult to understand grammar because of thetechnique which is used by the lecturer is not interesting; the students never practicetheir understanding in written; and learning technique which is used by the lectureris inappropriate with the subject. The objectives of this research are: to find out thestudents’ score in using jumble words technique; to find out the students’ score inusing word order technique; to find out the students’ score of grammar mastery; tofind out the students’ result of comparison of using jumble words and word ordertechniques toward students’ grammar mastery. The researcher conducts stratifiedrandom sampling design and pre-test and post-test control group design as researchinstrument. The result of hypothesis test on test phases both provides the differentresult which using significant degree 5%, where tcount is higher than ttable on theanalysis data of post-test with tcount =2,26 and ttable =2,02. It sows that The studentswho are taught by jumble word technique have higher score. In conclusion thatjumble words technique is more effective than word order technique in teachinggrammar mastery.